The Correlation Between Job Demand and Performance: An Empirical Analysis in a Higher Education Work Environment - A. Nur Asri Ainun; Muhammad Idrus Taba; Sumardi; Wahda (Association Of Indonesian Entrepreneurship Study Programs, 2024)
Enhancing lecturer performance is necessary to raise the standard of higher education. The purpose of this study is to assess the work requirements for instructors at Makassar City's private universities. job demands in this scenario encompass a variety of factors, including task ambiguity, time pressure and work overload. In this study, quantitative methodologies were applied. Teachers at several private universities in Makassar City received questionnaires. The analysis tool SPSS version 26 was used to examine the data that had been gathered. The study's findings demonstrated that role ambiguity significantly affected lecturers' performance. Time constraints and work overload have a beneficial but insignificant impact. Furthermore, compared to academics with less experience, lecturers with more experience typically exhibit superior job demand management skills